2017
DOI: 10.1097/cmr.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic review of negative sentinel lymph node biopsies in thin melanomas: an argument for the routine use of immunohistochemistry

Abstract: Sentinel lymph node biopsy (SLNB) is performed for some thin melanomas in the presence of concerning histopathological features. There are no defined standards for how sentinel nodes should be processed to detect microscopic metastases. We compared our method of serially sectioning nodes at 2-3 mm intervals and performing one hematoxylin and eosin (H&E) slide versus multiple H&E levels and utilizing immunohistochemistry (IHC). This was a retrospective review of a prospectively collected database identified pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Melan-A/Mart-1, and/or HMB-45 IHC on all sentinel nodes to maximize sensitivity as well as specificity for malignant cells. [23][24][25] These additional tissue levels examined by IHC also serve a second purpose of increasing the total amount of tissue of each sentinel node that is evaluated by histopathology. However, immunostains chosen for sentinel lymph node evaluation vary in their utility in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melan-A/Mart-1, and/or HMB-45 IHC on all sentinel nodes to maximize sensitivity as well as specificity for malignant cells. [23][24][25] These additional tissue levels examined by IHC also serve a second purpose of increasing the total amount of tissue of each sentinel node that is evaluated by histopathology. However, immunostains chosen for sentinel lymph node evaluation vary in their utility in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no current consensus on sentinel lymph node evaluation for melanoma, many institutions regularly perform S100, Melan‐A/Mart‐1, and/or HMB‐45 IHC on all sentinel nodes to maximize sensitivity as well as specificity for malignant cells 23‐25 . These additional tissue levels examined by IHC also serve a second purpose of increasing the total amount of tissue of each sentinel node that is evaluated by histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, institutional protocol for histopathological handling of sentinel lymph nodes and pathological reporting varies widely. 68,128,129,130,131,132 Macroscopically, two main methods of slicing sentinel lymph nodes exists: 'breadloafing', allowing for better examination of the subcapsular region, and bivalving, allowing for better examination of lymphatic vessels. 130,131 Both the European Organisation for Research and Treatment of Cancer (EORTC) and Sydney Melanoma Unit recommend the utilisation of the bivalving technique in sentinel lymph node histopathological and handling protocol.…”
Section: Discussionmentioning
confidence: 99%
“…68 The process of IHC staining, which may augment prognostication, is time-consuming and labourintensive. 128,129 IHC has been shown to mildly increase metastatic tumour detection rates in sentinel lymph nodes, but whether these mild increases justify the time and cost of performing IHC is controversial. 129 One study found that, although extensive IHC work-up may increase detection rates, survival is unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation